$dX_t = \delta dt+ 2\sqrt{X_t} dW_t$, where $W_t$ is a standard Wiener process,

Define $\tau =\frac{\sigma ^2}{2\nu(2 − \delta)}\left(1 − \exp \left(−\frac{2\nu t}{2−\delta}\right)\right)$

If $Y_t=\exp(\nu t) (X_\tau)^{1-(δ/2)}$, By Ito's Lemma,

$dY_t = \nu Y_t dt + \sigma Y_t^{(1−δ)/(2−δ)} dW_t $

But I cannot understand how Ito's Lemma can be applied here. My concern is that I have only learnt Ito's Lemma of $f(t,X_t)$, but now, $Y_t$ is a function of $t$ and $X_\tau$, but not $X_t$.

Thank you!


Since $$ e^{-\nu t}Y_t=X_{\tau}^{1-\frac{\delta}{2}}\,,\tag{1} $$

It$ô$'s lemma implies

$$ -\nu e^{-\nu t}Y_t\text dt + e^{-\nu t}\text dY_t = \text d(\color{red}{e^{-\nu t}Y_t}) = \text d(\color{red}{X_{\tau}^{1-\frac{\delta}{2}}}) = (1-\frac{\delta}{2})X_{\tau}^{-\frac{\delta}{2}}\text dX_{\tau}-\frac{1}{2}\frac{\delta(2-\delta)}{4}X_{\tau}^{-\frac{\delta+2}{2}}\text d\langle X\rangle_{\tau}\,. $$

Using the definition of $\ \text dX_{\tau}\ $simplifies this to $$ \text dY_t = \nu Y_t\text dt + e^{\nu t}(2-\delta)X_{\tau}^{\frac{1-\delta}{2}}\text dW_{\tau}\tag{2} $$

Finally, noting that $$ \int_{0}^{t}\sqrt{\frac{\text d\tau}{\text du}}\text dW_u \stackrel{\text{law}}{=} W_{\tau}\implies\text dW_{\tau}=\sqrt{\frac{\text d\tau}{\text dt}}\text dW_t = \frac{\sigma}{(2-\delta)}e^{-\frac{\nu t}{2-\delta}}\text dW_t\,, $$ together with (1), allows us to simplify (2) further. Thereby, we obtain $$ \text dY_t = \nu Y_t\text dt + \sigma e^{\nu t}e^{-\frac{\nu t}{2-\delta}}e^{-\frac{\nu t(1-\delta)}{2-\delta}}Y_t^{\frac{1-\delta}{2-\delta}}\text dW_{t} $$

This shows that

$$ \text dY_t = \nu Y_t\text dt + \sigma Y_t^{\frac{1-\delta}{2-\delta}}\text dW_{t} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.